Synergistic effect of Balanites aegyptiaca essential oil and storage materials on cowpea seeds - Feyisola F. Ajayi; Akama F. Ogori; Vivien O. Orede; Emmanuel Peter (Foods and Raw Materials, 2022)
The cowpea (Vigna unguiculata L.) is a legume produced and consumed all over Africa and especially in Nigeria. These beans are a major source of protein in the region. The cowpea weevil (Callosobruchus maculatus L.) is a major pest that affects cowpea seeds. Therefore, cowpea farmers need effective non-toxic pesticides to replace synthetic chemicals. The present research tested the effect of Balanites aegyptiaca L. essential oil on cowpea weevils. This research quantified weevil proliferation and cowpea seed qualities. The samples were treated with 5, 10, and 15 mL of B. aegyptiaca essential oil diluted in 1 mL of acetone and stored in five storage materials, i.e., jute bags, polythene bags, sacks, plastic containers, and glass bottles. The study featured a completely randomized design with three replications of each treatment: treatment time – 90 days, storage temperature – 30 ± 5°C, check – 0.125 g of aluminum phosphide, control – acetone. B. aegyptiaca essential oil proved to be an effective insecticide against cowpea weevils. The treatment achieved 100% mortality rate at 10 and 15 mL of B. aegyptiaca essential oil after 72 h of exposure in glass bottles, plastic containers, and jute bags. In addition, B. aegyptiaca essential oil demonstrated a potent activity against oviposition and survival of immature cowpea weevils. Cowpea seeds packaged in glass bottles, plastics containers, and jute bags showed significantly less damage than those stored in sacks and polythene bags. Glass bottles were the best storage material in terms of safety and shelf stability, followed by plastic containers and jute bags. B. aegeptica essential oil has potent insecticidal properties and can be used as pest control during grain storage.